Incidentally found rectal duplication during surgery for rectovestibular fistula and its management - Dhiraj K Balaji; Mamatha Basavaraju (Wolters Kluwer Medknow Publications, 2015)
Association of rectal duplication with rectovestibular fistula is rare. A 3-month-old patient underwent primary posterior sagittal anorectoplasty (PSARP) for rectovestibular fistula. During surgery the patient was found to have a rectal duplication (RD). We managed the case by excising the common wall and fenestrating the two lumens together and completed the PSARP.